Cash Waqf as an Alternative Source of Islamic Microfinance Institution’s Capital in Indonesia - Gustani, Gustani; Ernawan, Dwi Aditya (Journal of Islamic Economics Lariba, 2016)
One type of contemporary waqf is cash waqf. Cash Waqf provide more giving mashlahah because the money can be used for many things other than endowments. Form of cash waqf development is to be invested in Islamic financial institutions were profitable and secure. This paper aims to integrate the cash waqf as a social fund to the financial intermediation role on Islamic Micro Finance Institutions. Endowments in cash will be an alternative source of capital LKMS cheap and mashlahah. The pattern is divided into a cash waqf endowments temporary cash invested in sharia-term investment products, such as savings deposits and capital investments. Average cash waqf permanently included as a component of capital. Endowment funds will be disbursed on micro-finance, the results of which will be channelled to the social fund. With this pattern expected cash waqf and where LKMS can benefit the wider community.